Winter storms - Hilderbrand, Elin (Winter Street, 2016)
Some of the stormy weather of the past few seasons seems to have finally lifted for the Quinns. Kevin is about to tie the knot with Isabelle, and there's hopeful news about Bart, who has been captured by enemy forces in Afghanistan. That doesn't mean there aren't a few dark clouds on the horizon as the family juggle health scares and love triangles. But if there's one holiday that brings the Quinn family together, it's Christmas. And this year promises to be a celebration unlike any other as they prepare to host Kevin and Isabelle's wedding at the inn.